Answer:
z = -2
Step-by-step explanation:
Sbstitute it in for z in the equation.
Answer: E
Step-by-step explanation:
(3x^2 - 8) (3x^2 + 8)
You can get to the original equation by:
3x^2 * 3x^2 = 9x^4
-8 * 8 = - 64
9x^4 - 64
Answer:
E. (3x^2-8)(3x^2+8) is the correct answer.
Step-by-step explanation:
To factor this we use the differenceoftwosquaresformulabecause there are no common terms here.
9x^2-64
The square root of 9x^2= 3x^2
The square root of 64 is 8
(3x^2-8)(3x^2+8)
= 9x^2-64
You get back the answer. So it's correct.